1999
DOI: 10.1302/0301-620x.81b5.0810852
|View full text |Cite
|
Sign up to set email alerts
|

Financial justification for routine ultrasound screening of the neonatal hip

Abstract: When we add the cost of running the screening programme to the expense of treating the condition, the overall cost for the management of DDH is comparable for the different screening policies. [Br] 1999;81-B:852-7. J Bone Joint Surg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
(31 reference statements)
3
26
0
1
Order By: Relevance
“…This study shows higher initial costs caused by the ultrasound screening, but also a significant reduction in the total number and overall costs of dysplastic hips undergoing operative and non-operative treatment. Similar findings were reported by Clegg et al, 22 who compared the surgical costs of three screening methods for DDH: universal clinical examination alone, universal clinical examination with selective ultrasound examination for newborn babies with risk factors, and universal ultrasound screening. The mean costs per 1000 live births were £5110 for clinical investigation alone, £3811 for selective ultrasound screening, and £468 for universal ultrasound screening.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study shows higher initial costs caused by the ultrasound screening, but also a significant reduction in the total number and overall costs of dysplastic hips undergoing operative and non-operative treatment. Similar findings were reported by Clegg et al, 22 who compared the surgical costs of three screening methods for DDH: universal clinical examination alone, universal clinical examination with selective ultrasound examination for newborn babies with risk factors, and universal ultrasound screening. The mean costs per 1000 live births were £5110 for clinical investigation alone, £3811 for selective ultrasound screening, and £468 for universal ultrasound screening.…”
Section: Discussionsupporting
confidence: 84%
“…14 There is little published data concerning cost analysis when comparing clinical examination alone with clinical examination and ultrasound screening. [20][21][22] In the Austrian province of Tyrol, clinical examination alone was performed between 1978 and 1982. Between 1983 and 1988, a nationwide ultrasound screening programme according to Graf 6 was developed throughout Austria and since 1988 ultrasound screening has been performed for all newborn babies.…”
mentioning
confidence: 99%
“…As regards risk factors, females with a positive family history, and especially those born in the breech presentation, seem to have the highest risks. It is accepted that, scanning at birth, there will be numerous morphologically immature or unstable hips identified that will resolve spontaneously [139,145,146,147,148]. That is why we agree with authors who propose to postpone US in unselected infants beyond the neonatal period [145,149,150].…”
Section: Musculoskeletal Systemsupporting
confidence: 76%
“…Gray et al [18] calculated that in the sonography group the overall costs per patient were $190 less than those in the non-sonography group, but could not prove statistical significance. Clegg et al [8] [15,19,41] that document a significant reduction of treatment costs with a moderate increase of diagnostic expenses. The calculations on the overall financial burden of the Austrian Public Health System seem to decrease over the time.…”
Section: Discussionmentioning
confidence: 99%